PERAN UNESCO DALAM PERLINDUNGAN ANGKOR WAT SEBAGAI WARISAN BUDAYA DUNIA TAHUN 2009-2013 - Wijaya, Hendri; Dharmiasih, D.A. Wiwik; Kumala Dewi, Putu Ratih (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 1 (2016), 2016)
ABSTRACT Cambodia, as one of the countries that have ratified the 1972 UNESCO Convention Text has a famous World Cultural Heritage is Angkor Wat. As one of the World Cultural Heritage belongs to Cambodia, Angkor Wat has experienced variety of problems from lack of attention and management that lead to various problems for the continuity of Angkor Wat as a World Cultural Heritage site. To prevent further damage, UNESCO as an international organization to perform its role and together with the Government of Cambodia form two pieces of documents of cooperation. In 2009-2010 formed Cambodia-UNESCO country programming document which through this document plan framework further to protect Angkor Wat, namely Heritage Management Framework that formed in 2010-2013, established by UNESCO, the government of Cambodia and Australia. Heritage Management Framework provides a variety of management strategies and policies that are effective in the protection of Angkor Wat. This study aims to describe the role in the protection of Angkor Wat UNESCO as a World Cultural Heritage. This study use the concept of the role of UNESCO and the World Cultural Heritage. Locus of the study is from 2009 to 2013. Keywords: UNESCO, Angkor Wat, Protection, World Cultural Heritage